Vertical pipe in pipe marine riser - NRC tow tank experiments ... - Derradji-Aouat, A. (National Research Council of Canada. Institute for Ocean Technology, 2009)
Marine environments with harsh conditions such as those off the coast of Newfoundland and Labrador, NL, Canada, place serious operating and performance demands on offshore structures built for oil and gas production. Marine risers for floating offshore platforms in such harsh conditions are subjected to continuous and various forms of excitations and vibrations, induced by severe waves, strong currents, high winds, sea ice, and iceberg collisions. Vortex Induced Vibrations (VIV) enhance stress fatigue in marine risers and mooring systems, and consequently, shorten their expected design lifetime and increase the project’s overall capital cost. An alternate solution to the traditional “single pipe risers” is the use of pipe-in-pipe (PIP) marine risers. PIP design is based on the idea that an Inner Pipe (IP) and an Outer Pipe (OP), with floating spacers sandwiched in between, work together to reduce reacting/operating loads and fatigue stresses, increase the expected design lifetime of the riser, and maintain ...